The Global Minimum Tax Raises More Revenues than You Think, or Much Less - Eckhard Janeba; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2022)
The OECD's proposal for a global minimum tax (GMT) of 15% aims for a reversal of a decades-long race to the bottom of corporate tax rates driven by competition over real investments and profit shifting to low-tax jurisdictions. We study the revenue effects of the GMT by focusing on the induced strategic tax setting effects. The direct effect of the GMT is a reduction in profit shifting, which has a positive effect on revenues in high-tax countries as their tax base grows, and makes higher taxes attractive. A secondary effect, however, is that the value of attracting real foreign investments increases, which intensifies tax competition. We argue that the revenue effects of the GMT depend on the instruments governments use to attract firms. With endogenous corporate tax rates, revenues in non-havens increase if initially tax competition among non-havens is fierce. By contrast, when governments compete via lump sum subsidies, the revenue gains from less profit shifting are exactly offset by higher subsidies.
Keywords: F23; F55; H25; H73; 330; global minimum tax; tax competition; OECD BEPS; Pillar II